Neural network detection of grinding burn from acoustic emission - Wang, Zhen; Willett, Peter; Deaguiar, Paulo R. [UNESP]; Webster, John (Elsevier, 2001)
An artificial neural network (ANN) approach is proposed for the detection of workpiece `burn', the undesirable change in metallurgical properties of the material produced by overly aggressive or otherwise inappropriate grinding. The grinding acoustic emission (AE) signals for 52100 bearing steel were collected and digested to extract feature vectors that appear to be suitable for ANN processing. Two feature vectors are represented: one concerning band power, kurtosis and skew; and the other autoregressive (AR) coefficients. The result (burn or no-burn) of the signals was identified on the basis of hardness and profile tests after grinding. The trained neural network works remarkably well for burn detection. Other signal-processing approaches are also discussed, and among them the constant false-alarm rate (CFAR) power law and the mean-value deviance (MVD) prove useful.
Keywords: Acoustic emissions; Feature extraction; Hardness; Neural networks; Regression analysis; Steel; Theorem proving; Autoregressive (AR) coefficients; Mean-value deviance (MVD); Grinding (machining)